Successful Appendiceal Ureteral Substitution in a Rare Ureteric Involvement of Rhabdomyosarcoma in a Child - A Case Report - Ali Ariyono; Indrawarman Soerohardjo; Ahmad Zulhan Hendri (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Ureteral Rhabdomyosarcoma (RMS) in children is a rare malignancy that may involve the ureter, leading to obstruction and hydronephrosis. Management requires a combination of oncologic therapy and individualized surgical planning, particularly when tumor resection results in extensive ureteral defects. This case report describes an 8-year-old girl with pelvic embryonal RMS involving the right distal ureter, previously treated with pelvic radiotherapy and VAD (vincristine, actinomycin, and doxorubicin) chemotherapy. Imaging showed tumor compression of the distal ureter with grade III hydronephrosis. Surgical resection necessitated en bloc distal ureterectomy, creating a 10-cm ureteral defect. Due to prior pelvic radiation and concerns regarding bladder fibrosis and metabolic complications from bowel interposition, ureteral substitution using the appendix was performed. Postoperative recovery was uneventful, with stable renal function, normal electrolyte balance, and no urinary leakage. Follow-up imaging at 6 months demonstrated a well-functioning appendiceal conduit and no residual tumor. This case illustrates that appendiceal ureteral substitution can be a safe and effective reconstructive option for long distal ureteral defects in pediatric RMS, particularly when prior radiation limits alternative techniques. Careful surgical technique and close follow-up remain essential to ensure optimal outcomes Keywords: Ureteral Substitution, Ureteral Reconstruction, Appendix, Embryonal Rhabdomyosarcoma